1993
DOI: 10.1002/dvg.1020140606
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation in Drosophila spermatogenesis: Analysis of protein binding at the translational control element TCE

Abstract: We have previously identified a 12 nucleotide long sequence element, the TCE, that was demonstrated to be necessary for translational control of expression in the male germ line of Drosophila melanogaster (Schäfer et al., 1990). It is conserved among all seven members of the Mst(3)CGP gene family, that encode structural proteins of the sperm tail. The TCE is invariably located in the 5' untranslated region (UTR) at position +28 relative to the transcription start site. In this paper we analyse the mode of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
0
16
0
6
Order By: Relevance
“…6; Trpl). This indicated that the RNA-protein interaction does not solely depend on the primary sequence of the motif, as has been described for the translational control element binding site of the Mst(3)CPG gene family in spermatogenesis of Drosophila [23], but that the secondary structure of TNP2-3'UTR might be important as well. This was confirmed by analysis of the potential RNA structure of TNP2-3'UTR using the MFOLD computer program of Jaeger et al [22].…”
Section: Discussionmentioning
confidence: 79%
“…6; Trpl). This indicated that the RNA-protein interaction does not solely depend on the primary sequence of the motif, as has been described for the translational control element binding site of the Mst(3)CPG gene family in spermatogenesis of Drosophila [23], but that the secondary structure of TNP2-3'UTR might be important as well. This was confirmed by analysis of the potential RNA structure of TNP2-3'UTR using the MFOLD computer program of Jaeger et al [22].…”
Section: Discussionmentioning
confidence: 79%
“…Transgenic analysis has demonstrated convincingly that the TCE is required for translational control in vivo and that the position of the TCE in the 5Ј UTR is critical for translational repression. 28 TCE elements have been found in other Drosophila mRNAs as well, although their position within the 5Ј UTR does not appear to be conserved as stringently as that for the ( ) 29 Mst 3 CGP mRNAs. Similar elements in murine spermatogenic mRNAs have not been described.…”
Section: Regulatory Elements In the Mrnamentioning
confidence: 99%
“…The regulation of a family of mRNAs involved in spermatogenesis in Drosophila melanogaster, including Mst87F, is mediated by a conserved element in the 5' UTR of these mRNAs. As with ferritin, the position of this element with respect to the cap structure is conserved and movement of this element further downstream severely impedes regulation (Kempe et al, 1993). In addition, the mRNAs encoding different ribosomal proteins are translationally regulated via cap-proximal elements in many species, ranging from L32 in Saccharomyces cerevisiae (Dabeva and Warner, 1993) to L30, L32 and S16 in human cells (Levy et al, 1991).…”
Section: Regulation Of Ferritin and Ealas Mrnasmentioning
confidence: 99%